2021
DOI: 10.1371/journal.pone.0261712
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic significance of premature ventricular complexes in community and hospital-based participants: A scoping review

Abstract: Background While there are published studies that have examined premature ventricular complexes (PVCs) among patients with and without cardiac disease, there has not been a comprehensive review of the literature examining the diagnostic and prognostic significance of PVCs. This could help guide both community and hospital-based research and clinical practice. Methods Scoping review frameworks by Arksey and O’Malley and the Joanna Briggs Institute (JBI) were used. A systematic search of the literature using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“… 1 Our data complement these studies and provide strong evidence of a link between PACs in 15 s ECGs and incident AF. A recent systematic review on PVCs found four community-based studies reporting on standard 12-lead ECG, with some conflicting results, 3 , 10 , 25 , 27 and Nguyen et al 11 have recently shown that PVCs were associated with an increased risk of AF, HF, and mortality in CHS and ARIC cohorts.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Our data complement these studies and provide strong evidence of a link between PACs in 15 s ECGs and incident AF. A recent systematic review on PVCs found four community-based studies reporting on standard 12-lead ECG, with some conflicting results, 3 , 10 , 25 , 27 and Nguyen et al 11 have recently shown that PVCs were associated with an increased risk of AF, HF, and mortality in CHS and ARIC cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Since the CAST study, which is dated, research on the significance of PVCs has shifted in large part to outpatient populations, with a focus on the role that frequent PVCs might have on cardiomyopathies and/or HF (Marcus, 2020; Suba et al, 2021). Our study is unique in that no prior study has reported on six different PVC types and their association with VT in ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among community-dwelling populations of PWOH, VE has been reported as a surrogate marker of risk for adverse outcomes. 8 Studies show an association between increased frequency of PVCs and greater odds of a subsequent decrease in LVEF and incident HF independent of coronary heart disease. 7 , 29 Presence of PVCs also identifies a subset of otherwise low-risk individuals, including those without overt structural and functional LV abnormalities, as having higher risk for cardiovascular disease-related death including sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%